Menapaktilasi Perjalanan Hyang Nirartha: Potensi Wisata Spritual Di Kabupaten Buleleng - Ni Putu Rika Sukmadewi; Nyoman Dane; Luh Kartika Dewi (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
AbstractDang Hyang Nirartha's journey from Java to Bali left a number of stories and memories. Dang Hyang Nirartha is a figure who has a great influence on the development of religious forms in Bali. The Brahmins in Bali are his direct lineage, and to this day his figure Dang Hyang Nirartha has always been revered and cult. There are quite a lot of relics of Dang Hyang Nirartha in Bali, especially in Buleleng Regency, such as Pulaki Temple, Melanting Temple, Kayu Putih Temple, Ponjok Batu Temple, and others. The traces of Dang Hyang Nirartha's journey in several of these temples have not been developed optimally as was done at Uluwatu Badung Temple in Bali. The story of the holy journey carried out by Dang Hyang Nirartha can be used as a reference in developing tourist destinations in the form of literary tourism which is currently increasingly being looked at as an alternative tourism. Apart from being a holy priest, he was also a songwriter who was very famous in the era of the Gelgel kingdom. This paper will discuss the tourism potential that departs from the traces of Dang Hyang Nirartha in Buleleng Regency. The method used in this research is descriptive qualitative. All forms of data in the form of facts of historical places or locations related to the object of research are described and then used as objects of analysis. So that the results of this study are able to see the tourism potential of the Pulaki temple and Ponjok Batu temple as spiritual tourism based on literature and tourism.Keywords: Dang Hyang Nirartha, Tourism Potential, Spiritual Tourism